Heritage influences in the theater of Tawfiq al-Hakim Study of the play "People of the Cave" (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The recall of personalities, events or historical stages in a literary work in contemporary Arabic literature, is one of the most important phases of the relationship of the contemporary writer with his heritage, and the Koran is a source of creativity and expression of the Qur'anic personality or employment, and gives richness, authenticity and comprehensiveness of the writer's evidence. Since the religious heritage is closer to the collective memory, writers to this aspect accepted poetry and prose after the setback of June 1967, they came to the religious heritage inspired and inspired to inspire to be their literature documented relevance to society. The research came in four main ideas: the first in the Tawfiq al-Hakim theater, the second in inviting al-Hakim to find an Arab theater, and the third: in the statement of the idea of ​​the play of the people of the cave, and the fourth: to clarify the relationship between the play of the people of the cave and heritage, especially the Koran, through language and personalities Dialogue and conflict. إنَّ استدعاء الشّخصيّات أو الأحداث أو المراحل التّاريخيّة في عملٍ أدبيٍّ في الأدب العربيّ المعاصر ، هو من أهمِّ أطوار علاقة الأديب المعاصر بموروثه ، ويعدُّ القرآن من مصادر الإبداع والتّعبير بالشّخصيّة القرآنيّة أو توظيفها ، ويُعطي غنًى وأصالة وشمولاً لأدب الأديب . وبما أنَّ الموروث الدّينيّ أقرب إلى الذّاكرة الجماعيّة فقد أقبل الأدباء إلى هذا الجانب شعراً ونثراً بعد نكسة حزيران 1967م ، أقبلوا إلى التّراث الدّينيّ يستوحونه ويستلهمونه ليستثيروا الهمم وليكون أدبهم أوثق صلةً بالمجتمع . وجاء البحث في أربعة أفكارٍ رئيسةٍ : الأولى في مسرح توفيق الحكيم ، والثَّانية في دعوة الحكيم إلى إيجاد مسرحٍ عربيٍّ ، والثَّالثة : في بيان فكرة مسرحيّة أهل الكهف ، والرّابعة : في إيضاح العلاقة بين مسرحيّة أهل الكهف والموروثات التّراثيّة ، وخاصَّةً القرآن وذلك من خلال اللّغة والشّخصيّات والحوار والصّراع .